ZYNGBADPA’ an Effective Communication Tool in Cold Arid Ladakh - Kumar, Parveen; Lamo, Kunzang; F. D. Sheikh; D. Namgyal; Angchuk, Sonam (Journal of Agricultural Extension Management, 2021)
In recent years, Information and Communication Technologies (ICTs) have emerged as effective tools for the dissemination of information on a large scale to a large number of people. ICT is a broad term that encompasses simple mobile phones to computers and to satellite imageries. The use of ICTs can help to provide timely information to the farmers about the weather, outbreak of disease, crop management and market prices of various commodities. This paper illustrates how a simple device like a smart phone can serve the farming community. By creating a WhatsApp group ’ZYNGBADPA’, an array of diverse farming services from relevant advice and timely information regarding inputs, diseases and insect pest management to the weather condition and weather based agro advisories and from market information to marketing support is being provided to tribal communities in Leh district of Ladakh region. ’Zyngbadpa’ in Ladakhi language means one ’who works with the land’, i.e. a farmer